Islamic Religious Education Curriculum Management in Developing Religious Tolerance Attitudes - Aziz, Mursal; Napitupulu, Dedi Sahputra; Tanjung, Fitri Zahriani (Universitas Al-Amien Prenduan, 2025)
Instilling an attitude of religious tolerance from an early age is an urgent need in the context of a multicultural Indonesian society. However, in practice, various challenges are still found in elementary school environments, such as students' low understanding of the importance of tolerance and limited time and learning approaches used in Islamic Religious Education. This study aims to describe the PAI curriculum in developing students' religious tolerance attitudes at SDN 114339 Kuala Bangka. This study uses a qualitative field method with data collection techniques in the form of observation, interviews, and document studies. The results of the study indicate that Islamic Religious Education curriculum management plays an important role in developing students' religious tolerance attitudes. This is reflected in the planning process that involves the active role of teachers in providing role models and integrating Islamic values that uphold tolerance. In its implementation, learning methods are used that develop students' audio and visual abilities, such as making posters, showing videos, and writing short essays about tolerance. The obstacles faced include the diversity of students' backgrounds, their low understanding of tolerance, and the limited learning time which only takes place once a week.